Peran Islamic Social Reporting sebagai pemodaerasi profitabilitas, kebijakan dividen, dan leverage terhadap nilai perusahaan - Widayanti, Heni; Pratama, Abdul Aziz Nugraha (Nur Science Institute, 2022)
This study aimed to determine the effect of profitability, dividend policy, and leverage on firm value with Islamic Social Reporting as a moderator for companies on JII (Jakarta Islamic Indexes) in 2015-2019. The type of research used is quantitative, using secondary data. The sampling method is purposive sampling, with a total of 13 companies. The data analysis tool uses Moderated Regression Analysis. The results showed that profitability and dividend policy significantly positively affected firm value. Leverage does not affect firm value. The results of the moderation test show that the disclosure of Islamic Social Reporting can moderate the relationship between profitability and firm value. Disclosure of Islamic Social Reporting cannot moderate the relationship between dividend policy and leverage on firm value.